2018
DOI: 10.5505/tjtes.2018.48079
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Mortality in Acute Subdural Hematoma: Is Decompressive Craniectomy Effective?

Abstract: BACKGROUND: Despite rapid diagnosis and aggressive neurosurgical intervention, acute subdural hematoma (ASDH) is a severe type of head injury that can result in high morbidity and mortality. Although surgical procedures, such as craniotomy and decompressive craniectomy (DC), can be effective, the preferred approach for treating an ASDH remains controversial. The aim of this report was to evaluate factors associated with mortality in patients with ASDH and determinants of outcome in those with ASDH who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…34 DC has been shown to prevent brain damage, neurological worsening, and acute oedema following infarctions in patients with traumatic mass lesions. 35 All our patients underwent DC within 48 hours, and it is known that early DC within 48 hours has better neurological recovery and functional outcomes. [36][37][38] Additional factors concerning postoperative care shown to increase the risk of poor outcomes significantly include hypoxia, maintenance of cerebral perfusion pressure, and blood pressure when controlling for other important postoperative care covariates.…”
Section: Discussionmentioning
confidence: 89%
“…34 DC has been shown to prevent brain damage, neurological worsening, and acute oedema following infarctions in patients with traumatic mass lesions. 35 All our patients underwent DC within 48 hours, and it is known that early DC within 48 hours has better neurological recovery and functional outcomes. [36][37][38] Additional factors concerning postoperative care shown to increase the risk of poor outcomes significantly include hypoxia, maintenance of cerebral perfusion pressure, and blood pressure when controlling for other important postoperative care covariates.…”
Section: Discussionmentioning
confidence: 89%
“…The study is also in line with the conclusion that stated decompressive craniectomy can help prevent further midline shift and is associated with a lower mortality rate in comparison with craniotomy. 17 Research conducted by Phan, et al also mention that craniectomy is associated with poorer post-operative outcomes compared to craniotomy. 18 In a meta-analysis conducted by Mahadewa, et al in 2020, comparing GCS score between craniectomy and craniotomy in patients with traumatic acute subdural hematoma, revealed craniectomy had poorer clinical outcomes with a pooled risk ratio of 1.41 (95% CI: 1.06-1.88; p=0.02).…”
Section: Discussionmentioning
confidence: 99%
“…The topic of craniotomy or craniectomy for traumatic brain injury remains controversial and studies have shown contrasting results. 10,[12][13][14][15] However, the meta-analysis by Kevin Phan et al 10 concluded that when performed for acute subdural hematoma, decompressive craniectomy was found to be associated with a worse clinical outcome as compared to craniotomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Studies comparing DC with craniotomy in the management of traumatic brain injury have shown conflicting results with some studies finding DC to be associated with a better outcome and others finding DC to be associated with a worse prognosis. 10,[12][13][14][15] The two large decra and resuscip trial comparing DC with standard medical care in patients suffering from severe traumatic brain injury found that DC leads to more unfavorable outcome compared to standard medical management. 2 Making the procedure more controversial is the perception that even if DC reduces mortality it does so only by increasing the number of patients in the vegetative or severely disabled state, thus again putting into question the rationality of the procedure.…”
Section: Introductionmentioning
confidence: 99%